Process of Internationalizaiton of Chinese Firms --Case Studies of Haier and TCL - Hua, Ting (2006)
Since the global integration of the economic environment, internationalization has become one of the most popular topics with business research field. Internationalization phenomenon has received great research attention by considerable number of scholars over the last three decades. Most of their studies in this field were focus on the internationalization of developed regions rather than developing regions, because that the internationalization of developing regions was not the mainstream in this field two decades before. The situation nowadays is differently, the internationalization of developing regions has grown apace. So that it is time to fill this research gap in this field. Two of the most famous companies Haier and TCL in the Chinese household appliances industry are used as case examples of this research. The dissertation is aim to demonstrate the characteristics of the Chinese household appliances companies in different aspects of internationalization such as drives of internationalization, market selections, entry mode selections and barriers of entry. The aim has been achieved through comparison of empirical theory in this field and practice of the two cases, moreover, through the comparison of the practice of the two cases in different aspects of their internationalization. Furthermore, the internationalization process suitable for other Chinese household appliances companies has been addressed and recommendations in different aspects of internatiolizoant have been given.